Analisis Strategi Pengembangan Usaha Koperasi Produksi Susu Bogor, Jawa Barat - Abel Gandhy; Shinta Dewi Kurniawati (Universitas Proklamasi 45 Yogyakarta, 2018)
Total production of dairy farmers in Indonesia are accounted for less than a quarter of the national dairy consumption. Most of dairy farmers in Indonesia are coordinated by cooperative. Therefore, the right strategy is needed to strengthen the role of cooperatives and their members. Research is conducted in Bogor Dairy Production Cooperative (KPS Bogor), Bogor District. The research is offering Business Development Strategy of dairy cooperative using Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and Quantitative Strategic Planning Matrix (QSPM) methods. The results showed the internal and external (IE) indicators in KPS Bogor. IE Matrix showed that KPS Bogor stands in five quadrant. The general strategies are market penetration and product development. Based on matrix of SWOT method, there are six alternative strategies. QSPM results showed the highest priority strategy for KPS Bogor are: (1) Strategy to develop derivative products of milk, (2) Strategy to increase the number of dairy farmers, (3) Strategy to provide credit facilities for members of the cooperative, (4) Strategy to improve milk quality standards, (5) Strategy to expand the distribution network, and (6) Strategy to clarify goals of KPS Bogor.